2020
DOI: 10.1148/radiol.2019201326
|View full text |Cite
|
Sign up to set email alerts
|

Policies and Guidelines for COVID-19 Preparedness: Experiences from the University of Washington

Abstract: The coronavirus disease 2019 (COVID-19) pandemic initially manifested in the United States in the greater Seattle area and has rapidly progressed across the nation in the past 2 months, with the United States having the highest number of cases in the world. Radiology departments play a critical role in policy and guideline development both for the department and for the institutions, specifically in planning diagnostic screening, triage, and management of patients. In addition, radiology workflows, volumes, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 1 publication
(1 reference statement)
2
66
0
1
Order By: Relevance
“…CT scan is one of the modern diagnostic tools which can play a major role both in diagnosis of patients with high suspicion of COVID-19 and in the management of COVID-19 patients. In this study we mainly focused on the chest CT scan findings of 201 laboratory confirmed (RT-PCR) COVID-19 cases [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…CT scan is one of the modern diagnostic tools which can play a major role both in diagnosis of patients with high suspicion of COVID-19 and in the management of COVID-19 patients. In this study we mainly focused on the chest CT scan findings of 201 laboratory confirmed (RT-PCR) COVID-19 cases [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The chest CT features associated with COVID-19 demonstrated ground-glass opacities[ 74 ], reticular pattern[ 75 ], reverse halo sign[ 76 ], pleural effusion[ 77 ], paraseptal emphysema[ 78 ] and bronchial wall thickening[ 79 ]. Meanwhile, CT scans should be performed with strict safety measures to avoid unnecessary radiation and COVID-19 exposure to patients and the healthcare workforce[ 80 ]. Since COVID-9 is classified as a class B infectious disease, a high level of disinfection and sterilization processes need to be followed in the equipment operating room[ 81 ].…”
Section: Covid-19 Virus-host Interaction Mechanismmentioning
confidence: 99%
“…Effective internal communication has proved to be an essential tool in the guidance of all radiology personnel and the maintenance of good patient care during the pandemic. Communication goals 2) Departmental Communication: Weekly faculty meetings can communicate policies and updates for dissemination to the department-at-large, with updates from the crisis committee leadership (6). These meetings have gone from in-person meetings to virtual meetings.…”
Section: Communication During Times Of Crisismentioning
confidence: 99%